Implementation of Electronic Government as a Media of Information and Public Openness in Dadirejo Village, Wonosobo District, Tanggamus - Andreas Andoyo; Rani Ramadhani (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
Electronic government is a government-based electronic website, aiming to improve the relationship between the government and other parties. The e-government provides 24-hour online public services. The village of Dadirejo is a village located in the District of Tanggamus District, Dadirejo Village still has not used E-government as a public service, to overcome it in creating a new system that can be used as a medium of information to the public. The process of making E-government in Dadirejo Village is done by analyzing the existing system, then using some diagrams namely, DFD (Flow Diagram), ERD (Entity Relationship Diagram), and flow chat. Continued premises designing web and MySQL database. E-government in Dadirejo Village is expected to make it easier to provide services and information to the community quickly, accurately, and indefinitely